AUDIT KAS KELUAR DAN KAS MASUK PADA KPRI ANGKASA DI KAP INARESJZ KEMALAWARTA YANG BELUM TERKOMPUTERISASI - Rosa Nikmatul Fajri, Dimas Ilham Rois (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2020)
Audit of cash balances aims to obtain evidence about each significant assertion relating to cash balance transactions. Assertions used determine the audit objectives for cash balances are a) the existence and occurrence: whether the entity's assets or liabilities actually exist on a certain date and whether the transactions recorded have actually occurred during a certain period; b) completeness: whether all transactions and accounts that must be presented in the financial statements have actually been included; c) rights and obligations: whether the asset has become the entity's rights and liabilities have indeed become the entity's obligations on a certain date; d) appraisal or allocation: whether the components of assets, liabilities, income and expenses have been included in the appropriate amount of financial statements and presentation or disclosure: whether certain components of financial statements have been classified, described and properly disclosed. Research written in the form of a case study is one of the studies applied to applied research with an intensive focus and this study was carried out to find out the occurrences of events that occurred and provide solutions to the events that occurred, in this study usually in the form of descriptive. In this study it can be concluded that there is an error in the serial number of evidence, the materiality level of cash out and cash in does not exceed 10% or not materiality because it does not affect the overall financial statements, the risk of cash out and cash in is classified as low risk due it can be completed.